A atuação cristã perante o poder islâmico em córdoba de meados do Século IX: os mártires voluntários de córdoba - Silva, Fabrício De Lima Patu E (2018)
Through the research concerning the resistance of the Mozarabs to the Islamic yoke in Al Andaluz, this dissertation aims to show aspects of the coexistence between two distinct cultures, Christian and Islamic, which occurred in the Iberian Peninsula, more precisely in the South of Spain, a region that was the scene of the encounter and coexistence between Islamists and Christians. The object of study is limited to the period extending from the 8th to the 9th century, having as specific place the city of Cordoba, the capital of the emirate at that time. It is intended to present and analyze some of the clashes between the two cultures, specifically the movement known as the martyrs of Cordoba, whose founder and propagator was Eulógio, the bishop of Cordoba, who inspired the Christian martyrs of the early Christian times, encouraged and disseminated in Córdoba a movement of Christian reaction against the pressure imposed on them by Islamic power. From 850 to 859, 48 faithful voluntarily reached martyrdom. As a source for the proposed study, we use the writings of Saint Eulogy of Córdoba present in the complete works of San Eulógio de Córdoba Pedro Herrera Roldán.